Usefulness of FRAIL Scale in Heart Valve Diseases - Duchnowski, Piotr (Clin Interv Aging, 2020)
BACKGROUND: The frailty syndrome is a serious health problem for an aging population. The occurrence of frailty in the group of symptomatic patients undergoing heart valve surgery may have additional clinical implications. The predictive ability of the FRAIL scale in patients undergoing heart valve surgery during a 30-day follow-up has not yet been described. PATIENTS AND METHODS: A prospective study was conducted on a group of consecutive patients with hemodynamically significant valve disease (aortic stenosis, aortic regurgitation, mitral stenosis and mitral regurgitation) that underwent elective valve surgery in 2014–2019. The primary endpoint was 30-day mortality. Univariate analysis, followed by multivariate regression analysis, was performed. RESULTS: The study group included 672 consecutive patients (aortic valve stenosis, aortic regurgitation, mitral stenosis and mitral regurgitation) who underwent replacement or repair of the valve. Twenty-five patients died during the 30-day follow-up. At multivariate analysis, FRAIL scale result (OR 2.802; 95% CI 1.275–6.157; p=0.01) and red cell distribution width (RDW) (OR 1.810; 95% CI 1.181–2.775; p=0.006) remained independent predictors of the primary endpoint. CONCLUSION: The presented study showed the predictive ability of the FRAIL scale result in patients undergoing heart valve surgery for 30-day mortality.